SUKU BUNGA DITURUNKAN, INVESTASI AKAN MENINGKAT ? - Iswardono Iswardono (Journal of Indonesian Economy and Business (JIEB), 1999)
This paper examines whether reduction in discount rate would spur investment in Indonesia. This analysis is substantial; since there is an increasing demand from business people and economists, aimed to Bank of Indonesia, to reduce the SBI (Bank of Indonesia Certificate) rate. In this regard, the paper initially reviews several factors affecting investment: changes in the production function, relative price, discount rate, risk, and demand. Several empirical studies associated with investment function are also depicted in the paper. Several limitations in the Indonesian investment model are then followed. Eventually; this paper concluded that reduction in credit discount rate trough SBI does not necessarily affect investment, since investors are more concerned with risk factors underlining their future economy. Therefore; the government needs to induce a more transparent and certain condition, and hence provides a more perfect information for the business people to make clearer investment decisions.